Surgical treatment of fractures of the zygomaticomaxillary complex: effect of fixation on repositioning and stability. A systematic review. Issue 4 (May 2022) - Raghoebar, Iva I.; Rozema, Frederik R.; de Lange, Jan; Dubois, Leander
Abstract: Management of zygomaticomaxillary complex (ZMC) fractures can be challenging. Consequently, there is a difference in treatment amongst clinicians. In the literature it remains unclear if the number of fixation points affects the quality of the anatomical reduction, stability through time, and potential complications. Therefore, the objective of this study was to assess the outcome of no fixation, one-point fixation and multiple-point fixation of ZMC fractures. MEDLINE, EMBASE and The Cochrane Central Register of Controlled Trials were searched to identify eligible studies. After screening 925 articles, 17 studies fulfilled the inclusion criteria. Based on this systematic review no clear conclusions can be drawn on how stability, repositioning, and postoperative complications are affected by the number of fixation points. Nevertheless, it can be concluded that the advantage of multiple approaches is direct visualisation, and the downside is potentially approach-related complications. This review suggests that intraoperatively assisted cone-beam computed tomography (CBCT) can help improve the quality of the repositioning and by minimising the number of fixation points, the number of postoperative complications could be further reduced.